LOVE DIVINATIONS OF THE CROATS IN THE CONTEXT OF THE EUROPEAN CULTURAL HERITAGE - Dragic, Marko (European Scientific Journal, ESJ, 2014)
The paper carries about ten love divinations of the Croats published in the scientific literature. It also contains about thirty modern original field records of examples of love divinations. Love divinations are of ancient origin, and are associated with Christian feasts. Most divinations are associated with St George’s Day, the Nativity of St John the Baptist, and St Lucia’s Day. Love divinations of the Croats are also associated with the following feasts: All Saints’ Day, feast of St Andrew, feast of St Thomas, feast of St Sylvester (New Year’s Eve) and Ash Wednesday. Of the given examples of love divinations, according to the testimonies in the field, here and there a custom has survived to write the names of the persons you feel a liking for down on twelve small slips of paper on St Lucia’s Day. In addition to Croatian love divinations, the paper also brings a few Bosniac, Serb, Polish and Italian love divinations. The said love divinations contain an exceptional ethnological and anthropological treasure. The average age of tellers is 69 years. This warns us that a large number of love divinations, as well as of immaterial cultural heritage in general, have fallen irretrievably into oblivion.